FORUM SHOPPING EVIDENCE IN THE WORLD TRADE ORGANIZATION: A SOCIAL NETWORK ANALYSIS OF DISPUTES BETWEEN MEMBER STATES - Freitas, Kenyth Alves de; Vilela, Bruno de Almeida; Ferreira, Rui Fernando Correia; Aprigio, André Edson Ribeiro de Souza (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
The intensification of trade between countries has led to the need to regulate the conduct of trading partners. The World Trade Organization (WTO) forum emerged with the mission of arbitrating these disputes and making trade fairer. However, many countries choose not to participate in this forum because of the financial and legal resources required to conduct the proceedings. The purpose of this research was to verify how the relations within the WTO were configurated in 2014. We identified the dichotomy between central and emerging countries through the concept of forum shopping. The most important actors in the network were shown to be the United States and the European Union, whereas small economies had low participation, especially African and Central American countries. Thus, this study shows that many WTO’s members do not use its forum, which allows inferring they choose regional forums due to the restriction of resources.